Salsolinol Attenuates Doxorubicin-Induced Chronic Heart Failure in Rats and Improves Mitochondrial Function in H9c2 Cardiomyocytes - Wen, Jianxia; Zhang, Lu; Liu, Honghong; Wang, Jiabo; Li, Jianyu; Yang, Yuxue; Wang, Yingying; Cai, Huadan; Li, Ruisheng; Zhao, Yanling (Frontiers in Pharmacology, 2019)
Backgrounds: Salsolinol (SAL), a plant-based isoquinoline alkaloid, was initially isolated from Aconiti Lateralis Radix Praeparata (ALRP) and identified as the active cardiotonic component of ALRP. This study was aimed to explore the therapeutic effect and mechanism by which SAL attenuates doxorubicin (DOX)-induced chronic heart failure (CHF) in rats and improves mitochondrial function in H9c2 cardiomyocytes. Methods: Rats were intraperitoneally injected with DOX to establish CHF model. Therapeutic effects of SAL on hemodynamic parameters, serum indices and the histopathology of the heart were analyzed in vivo. Moreover, H9c2 cardiomyocytes were pretreated with SAL for 2h before DOX treatment in all procedures in vitro. Cell viability, cardiomyocyte morphology, proliferation, and mitochondrial function were detected by a high content screening (HCS) assay. In addition, a Seahorse XFp analyzer was used to evaluate the cell energy respiratory and energy metabolism function. To further investigate the potential mechanism of SAL, relative mRNA and protein expression of key enzymes in the tricarboxylic acid cycle in vivo and mitochondrial calcium uniporter (MCU) signaling pathway-related molecules in vitro were detected. Results: The present data demonstrated the pharmacological effect of SAL on DOX-induced CHF, which was through ameliorating heart function, down-regulating serum levels of myocardial injury markers, alleviating histological injury to the heart, increasing the relative mRNA expression levels of key enzymes downstream of the tricarboxylic acid cycle in vivo and thus enhancing myocardial energy metabolism. In addition, SAL had effects on increasing cell viability, ameliorating DOX caused mitochondrial dysfunction, increasing mitochondrial oxygen consumption rate (OCR) and extracellular acidification rate (ECAR) in H9c2 cardiomyocyte. Moreover, we found that SAL might have an effect on improving mitochondrial respiratory function and energy metabolism via inhibiting excessive activation of MCU pathway in heart tissue. However, the protective effect could be ameliorated by ruthenium red (an MCU inhibitor) and abrogated by spermine (an MCU activator) in vitro. Conclusion: The therapeutic effects of SAL on CHF is possibly related to ameliorating cardiomyocyte function resulting in promoting mitochondrial respiratory and energy metabolism. Furthermore, the potential mechanism might be related to downregulating MCU pathway. These findings may provide a potential therapy for CHF.